1988
DOI: 10.1113/jphysiol.1988.sp017349
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐cell recordings of ionic currents in bovine somatotrophs and their involvement in growth hormone secretion.

Abstract: SUMMARY1. The whole-cell mode of the patch-clamp technique was used to record voltage-activated cationic currents in immunocytochemically identified bovine somatotrophs.2. In current-clamp mode, cells had a resting membrane potential of -83-0+ 4-5 mV, and an input resistance of 8-4 + 2-1 GS2. Cells rarely fired action potentials spontaneously, but fired one to three action potentials in response to a suprathreshold current pulse.3. Under voltage clamp, in Ca2+-free media, the action potential was shown to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
(60 reference statements)
3
34
1
Order By: Relevance
“…Nevertheless, the resting membrane potential reported here is similar to that reported for gonadotrophs in other species recorded under similar conditions. Similar to ovariectomized female rat gonadotrophs , rat somatotrophs (Chen et al 1990), and melanotrophs (Stack and Surprenant 1991), as well as frog melanotrophs (Valentijn et al 1991), but unlike bovine somatotrophs (Mason and Rawlings 1988) and ovine gonadotrophs (Mason and Waring 1985), goldfish gonadotrophs did exhibit spontaneous action potential firing when held at their resting membrane potential. In addition, in response to depolarizing current injections, one or more action potentials could be elicited in goldfish gonadotrophs.…”
Section: Electrical Membrane Propertiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, the resting membrane potential reported here is similar to that reported for gonadotrophs in other species recorded under similar conditions. Similar to ovariectomized female rat gonadotrophs , rat somatotrophs (Chen et al 1990), and melanotrophs (Stack and Surprenant 1991), as well as frog melanotrophs (Valentijn et al 1991), but unlike bovine somatotrophs (Mason and Rawlings 1988) and ovine gonadotrophs (Mason and Waring 1985), goldfish gonadotrophs did exhibit spontaneous action potential firing when held at their resting membrane potential. In addition, in response to depolarizing current injections, one or more action potentials could be elicited in goldfish gonadotrophs.…”
Section: Electrical Membrane Propertiesmentioning
confidence: 88%
“…Similarly, voltage-dependent Na + currents were observed in general populations of goldfish pituitary cells (Price et al 1993), rat somatotrophs (Chen et al 1990), and a cell line of gonadotroph lineage (Bosma and Hille 1992), as well as rat (Tse and Hille 1993) and ovine (Mason and Rawlings 1988) gonadotrophs. Compared with other vertebrate gonadotrophs, Na + currents in goldfish gonadotrophs activated at similar potentials to those of female rats (Tse and Hille 1993) but at more depolarized potentials than ovine gonadotrophs (Mason and Sikdar 1988) or gonadotroph cell lines (Bosma and Hille 1992).…”
Section: Ionic Currentsmentioning
confidence: 89%
“…On the other hand, the long-term effects of ghrelin and GHRPs on GH secreting cells remain virtually unexplored. Nevertheless, it has been suggested that voltage-activated Ca 2+ channels play a key role in the regulation of GH secretion Mason and Rawlings 1988;Nussinovitch 1989;, and two types of voltage-activated Ca 2+ currents have been described in somatotropes (Lewis et al 1988;Mason and Rawlings 1988;) similar to the low voltage-activated (LVA) and high voltage-activated (HVA) Ca 2+ currents found in many different cell types (Hille 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Most of our knowledge to date about the properties of voltage-gated calcium channels in anterior pituitary cells has been obtained from neoplastic cell lines (Hagiwara & Ohmori, 1982;Matteson & Armstrong, 1984), although work on isolated, characterized pituitary cells is beginning to emerge, mainly on lactotrophs and somatotrophs (Cobbett, Ingram & Mason, 1987;Mason & Rawlings, 1988). The main factor which has hampered work on gonadotroph electrophysiology has been the difficulty in obtaining a gonadotroph-rich cell population.…”
Section: Introductionmentioning
confidence: 99%